War and peach - Furlong, Susan (Mystery writer) (Furlong, Susan (Mystery writer) Georgia peach mystery., 2017)
When one of the mayoral candidates, local farmer Clem Rogers, is murdered, all eyes turn to his rival--small-business owner Margie Price--and it is up to Nola Mae Harper to find the truth before the killer casts another fatal vote.